EXPERIMENTAL AND ANALYTICAL STUDY ON THE IMPACT BEHAVIOR OF STEEL–CONCRETE COMPOSITE SLAB (Advances in Civil and Architectural Engineering, 2021)
Concrete structures have been widely used for many years to resist impact loads. Steel–concrete composite structures may be considered efficient structures in the emerging modern construction field. Hence, the main objective of this research was to study the impact behavior of steel concrete composite slabs with different shear connectors and compare them with conventional slabs. Seven specimens of dimensions 500 × 500 × 50 mm were cast, which included plain cement concrete slabs, two reinforced cement concrete slabs with steel mesh and steel rebars as reinforcement, and four steel-concrete composite slabs with four different shear connectors: stud, tee, angle, and channel connectors. The composite action was achieved using a steel decking sheet welded with connectors on which the concrete layer was poured at the top. The test setup was fabricated with slots provided for specimens with simply supported end conditions and a mild steel drop weight. The specimens were impacted at the center of the span by dropping a steel mass from a free fall height of 1 m. The number of blows corresponding to the initial cracking and ultimate failure stages was recorded. The parameters that were used to compare the specimens were the impact energy absorbed, crack pattern, crack width, and increase in impact energy from the first blow to the last blow. The experimental results were very close to the analytical results obtained using ANSYS. The experimental and analytical results showed that the composite slabs with channel connectors performed better than the others, and it was proven that the composite slabs performed better under impact loading than conventional slabs.